Pelatihan Literasi Hukum Masyarakat terhadap Ranperda Kawasan Tanpa Rokok melalui Program Pengabdian Perguruan Tinggi di Kota Medan - Harahap, Muslim; Sitorus, Andi Putra; Pratitis, Sugih Ayu; Sinaga, Dearma; Munthe, Gerald Elisa (Civiliza Publishing, 2025)
This research aims to increase public legal literacy towards the Ranperda of Non-Smoking Areas (KTR) through university service programs in the city of Medan. The approach used is qualitative descriptive with the subject of people living or active in the target area of the Ranperda KTR. Data was collected through training and workshops on legal rights, obligations, and sanctions, pre- and post-training questionnaires, and participatory observation to assess community response and participation. The results of the study show that legal literacy training has proven to be effective in increasing public understanding of the Ranperda KTR, increasing awareness of legal compliance, and encouraging active participation in supervision and implementation of regulations. Based on these findings, it is recommended that legal literacy programs be carried out routinely with interactive methods, supported by local governments through socialization and public facilities that facilitate compliance with the KTR. This research shows that educational and participatory-based community service is an effective strategy to strengthen legal compliance while creating a healthier environment.